Burung Sebagai Atraksi Ekowisata di Kawasan Pariwisata Nusa Dua, Bali - A. A. G. Raka Dalem; I K. Muksin; S. K. Sudirga; I. B. M. Suaskara (Bumi Lestari Journal of Environment)
A study on birds has been conducted in Nusa Dua Tourist Resort area, Bali, betweenJanuary, 1999 and January, 2002. In this study, bird species was identified and theirpotentials for ecotourism-bird watching activities were analysed. From the field observationit was found that the site has a potential to be developed as a bird watching site. It can beseen from the diversity of bird species identified there, especially in the lagoon. In Nusa DuaTourist Resort area 83 bird species has been identified which is representing over 27% ofbird species on Bali. About 87% of those were classified as non-migrant species, while therest were migrant. Among those species, 6% were birds which were known to be restrictedtheir distribution to Indonesia. The strategic location of Nusa Dua Tourist Resort area alsoincreases its potential for development of bird watching activities. For development of theseactivities, holistic management approaches need to be implemented, the approaches of whichneed considering a balance between conservation, economic and empowerment of localcommunity objectives.